Ergonomic Redesign of a Traditional Fishing Vessel Wheelhouse Using Anthropometric Data and Postural Analysis - Wiediartini; George Endri Kusuma; Haidar Natsir Amrullah; Moch. Luqman Ashari; Lukman Handoko (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
The ship's wheelhouse is a critical control center, yet its design often neglects essential ergonomic principles. This study analyzes the ergonomic aspects of the wheelhouse on a traditional fishing vessel, a type commonly used in the coastal areas of northern Java, Indonesia. The ergonomic evaluation of the design involved a quantitative postural analysis using the Rapid Upper Limb Assessment (RULA) method. The initial assessment revealed a RULA score of 3, indicating a need for ergonomic intervention, primarily due to issues with arm and wrist postures. In response, a redesign was proposed using Indonesian anthropometric data and simulated with CATIA software. The redesign included modifications to the console height, steering wheel dimensions, and the layout of the control panel. Validation using a Digital Human Model (DHM) showed a significant improvement, with the RULA score decreasing to 1 for the steering task and score 2 for reaching the control lever, indicating an acceptable postural load. The study concludes that applying anthropometric data to the wheelhouse design can substantially enhance operator safety, comfort, and productivity.